2015
DOI: 10.1155/2015/463530
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Methyleugenol on IgE‐Mediated Allergic Inflammation in RBL‐2H3 Cells

Abstract: Allergic diseases, such as asthma and allergic rhinitis, are common. Therefore, the discovery of therapeutic drugs for these conditions is essential. Methyleugenol (ME) is a natural compound with antiallergic, antianaphylactic, antinociceptive, and anti-inflammatory effects. This study examined the antiallergic effect of ME on IgE-mediated inflammatory responses and its antiallergy mechanism in the mast cell line, RBL-2H3. We found that ME significantly inhibited the release of β-hexosaminidase, tumor necrosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 29 publications
(35 reference statements)
1
20
0
Order By: Relevance
“…The release of inflammatory mediators and cytokines from immune cells has been implicated in Type-I allergy. Further, it is reported that TNF-α and COX-2 play an important role in AD like allergic responses (Fogh, Herlin, & Kragballe, 1989;Tang et al, 2015). Here, we found that GFE inhibited the production of COX-2 and TNF-α in stimulated RBL-2H3 cells (Figure 2(A)).…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…The release of inflammatory mediators and cytokines from immune cells has been implicated in Type-I allergy. Further, it is reported that TNF-α and COX-2 play an important role in AD like allergic responses (Fogh, Herlin, & Kragballe, 1989;Tang et al, 2015). Here, we found that GFE inhibited the production of COX-2 and TNF-α in stimulated RBL-2H3 cells (Figure 2(A)).…”
Section: Resultssupporting
confidence: 61%
“…After synthesis, β-hexosaminidase is stored in secretory granules and released into the extracellular medium during degranulation. RBL-2H3 cells were grown in 24-well plates (2.5 × 10 6 cells per well) and were sensitized overnight with 10 μg/mLof DNP-IgE (Tang et al, 2015). Next, the growth medium was replaced with modified Siraganian buffer (119 mmol/L NaCl, 5 mmol/L KCl, 1 mmol/L CaCl 2 , 0.4 mmol/L MgCl 2 , 25 mmol/L PIPES, 5.6 mmol/L glucose, 40 mmol/L NaOH, and 0.1% [w/v] BSA, pH 7.2).…”
Section: β-Hexosaminidase Release Assaymentioning
confidence: 99%
“…26 Methyleugenol has been demonstrated to reduce the IgE-mediated allergic inammation in mast cells. 27 Camphene has been reported to inhibit the LPS-induced TNF-a production in the RAW264.7 macrophages. 28 a-Terpineol suppresses the production of inammatory mediators in LPS-stimulated human macrophages by regulating NF-kB and MAPKs.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, several of proinflammatory cytokines and allergic mediators are released, leading to immune response. Histamine and β -hexosaminidase are commonly considered as the notable markers in degranulation of mast cells [ 17 ]. Previous reports have demonstrated that they would be elevated in plasma or tissues in various allergic diseases.…”
Section: Discussionmentioning
confidence: 99%